2019
DOI: 10.1016/j.hpb.2019.03.139
|View full text |Cite
|
Sign up to set email alerts
|

Folfirinox is associated with a long-term survival benefit compared to gemcitabine-abraxane for neoadjuvant therapy before pancreatic cancer surgery

Abstract: Background: Peri-operative pain management around the time of hepato-pancreatic (HP) surgery has been debated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Both oxaliplatin, irinotecan, fluorouracil, and leucovorin (FOLFIRINOX) and gemcitabine plus nab-paclitaxel (GA) are suggested by clinical practice guidelines as first-line therapies for patients with BRPC and LAPC, given data from two phase III clinical trials that demonstrated longer overall survival in metastatic PC patients treated with either FOLFIRINOX or GA than in those treated with gemcitabine alone (13,14). Currently, although several studies have compared the efficacy of FOLFIRINOX and GA in localized PC, no consensus has been reached (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both oxaliplatin, irinotecan, fluorouracil, and leucovorin (FOLFIRINOX) and gemcitabine plus nab-paclitaxel (GA) are suggested by clinical practice guidelines as first-line therapies for patients with BRPC and LAPC, given data from two phase III clinical trials that demonstrated longer overall survival in metastatic PC patients treated with either FOLFIRINOX or GA than in those treated with gemcitabine alone (13,14). Currently, although several studies have compared the efficacy of FOLFIRINOX and GA in localized PC, no consensus has been reached (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that FOLFIRINOX prolongs survival more than GA (19,21,22), while others showed that the efficacy of these two regimens is similar (16)(17)(18)20,23).…”
Section: Introductionmentioning
confidence: 99%